Study of laminar combustion characteristics of gasoline surrogate fuel-hydrogen-air premixed flames. (21st May 2019) - He, Xu; Hou, Xinghe; Yang, Qing; Ma, Xiqun; Tian, Guohong; Liu, Fushui
Abstract: This paper investigated the effects of hydrogen addition to gasoline surrogates fuel-air mixture on the premixed spherical flame laminar combustion characteristics. The experiments were carried out by high speed Schlieren photography on a constant-volume combustion vessel. Combining with nonlinear fitting technique, the variation of flame propagation speed, laminar burning velocity, Markstein length, flame thickness, thermal expansion coefficient and mass burning flux were studied at various equivalence ratios (0.8–1.4) and hydrogen mixing ratios (0%–50%). The results suggested that the nonlinear fitting method had a better agreement with the experimental data in this paper and the flame propagation was strongly effected by stretch at low equivalence ratios. The stretched propagation speed increased with the increase of hydrogen fraction at the same equivalence ratio. For a given hydrogen fraction, Markstein length decreased with the increase of equivalence ratio; flame propagation speed and laminar burning velocity first increased and then decreased with the increase of equivalence ratio while the peaks of the burning velocity shifted toward the richer side with the increase of hydrogen fraction. Highlights: Laminar flame of TRF-hydrogen-air mixture was studied. Flame speed increases with the hydrogen addition ratio increases. The nonlinear fitting could achieve higher accuracy compared to linear one. The effects of hydrogen on rich and lean mixtures' flame stability were opposite.